Human Epididymis Protein 4 Inhibits Proliferation of Human Ovarian Cancer Cells Via the Mitogen-Activated Protein Kinase and Phosphoinositide 3-Kinase/AKT Pathways. Issue 3 (1st March 2014) - Kong, Xiuli; Chang, Xiaohong; Cheng, Hongyan; Ma, RuiQiong; Ye, Xue; Cui, Heng
Abstract : Objectives: Human epididymis protein 4 (HE4) is a promising novel biomarker for the detection of epithelial ovarian cancer (EOC). The role of HE4 in EOC tumorigenesis is unclear. This study investigated the cellular and molecular mechanisms of HE4 in ovarian cancer cell proliferation. Methods: We generated HE4-overexpressing SKOV3 cells and silenced HE4 gene expression in SKOV3.ip1 cells. We used the cell counting kit 8 assay to evaluate cell proliferation and Western blotting to analyze the expression of proliferation- and apoptosis-associated proteins such as Bax, Bcl-2, and caspase 3. Results: Overexpression of HE4 in SKOV3, an ovarian carcinoma cell line, inhibited cell proliferation, In contrast, HE4 silencing in SKOV3.ip1 cells promoted cell proliferation; however, conditioned medium containing HE4 and human recombinant HE4 protein had no effect on proliferation in both SKOV3 and SKOV3.ip1 cells. Human epididymis protein 4 inhibited MEK, extracellular signal–regulating kinase 1/2, and AKT phosphorylation but promoted c-Jun N-terminal protein kinase 1/2/3 and c-JUN phosphorylation; however, p38 phosphorylation was impaired in HE4-overexpressing and silenced cells. Human epididymis protein 4 had no effect on epidermal growth factor receptor phosphorylation or on the apoptosis-associated proteins Bax, Bcl-2, and caspase 3. Conclusions: Human epididymis protein 4 might play a protective role in the progression of EOC by inhibiting cell proliferation. Antiproliferative activity was mediated by intracellular HE4 and not the secreted protein. Human epididymis protein 4 might inhibit cell proliferation by regulating the mitogen-activated protein kinase and phosphoinositide 3-kinase/AKT signal transduction pathways in vitro.